2019
DOI: 10.1080/00288233.2019.1680395
|View full text |Cite
|
Sign up to set email alerts
|

Can alternative forages substantially reduce N leaching? findings from a review and associated modelling

Abstract: Nitrogen (N) leaching losses from grazed pasture systems pose a risk to the environment with mitigation strategies urgently required to achieve regulatory limits. There has been increased interest in alternative forages to manipulate excretion of urinary-N of livestock. This review summarises research on key forage attributes which affect the pattern of urine-N excretion. The literature showed an opportunity to alter both N concentration and moisture concentration of forages to reduce urine patch N loading. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 99 publications
1
34
0
1
Order By: Relevance
“…The challenges of maintaining productivity while meeting regulations for improved environmental outcomes and reducing water usage in pasture-based systems in New Zealand relying on perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) highlights the need to consider the role of alternative forages in facing these issues. Recent research has shown environmental benefits from forages based on a range of plant traits including winter activity for reduced nitrate Plants 2020, 9, 611 2 of 18 leaching [1]; high moisture content to reduce urinary nitrogen load [2]; low fibre content to reduce methane [3], and increased soil water use to reduce drainage [4,5]. Forage herbs such as chicory (Cichorium intybus L.) possess many of the attributes required to improve pastoral farm systems.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges of maintaining productivity while meeting regulations for improved environmental outcomes and reducing water usage in pasture-based systems in New Zealand relying on perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) highlights the need to consider the role of alternative forages in facing these issues. Recent research has shown environmental benefits from forages based on a range of plant traits including winter activity for reduced nitrate Plants 2020, 9, 611 2 of 18 leaching [1]; high moisture content to reduce urinary nitrogen load [2]; low fibre content to reduce methane [3], and increased soil water use to reduce drainage [4,5]. Forage herbs such as chicory (Cichorium intybus L.) possess many of the attributes required to improve pastoral farm systems.…”
Section: Introductionmentioning
confidence: 99%
“…The interest within New Zealand in mitigating N 2 O and NO − 3 has generated a significant body of research some of which is presented here. In this special issue, two reviews have synthesised the current knowledge of the role that plants, commonly used in pastoral and mixed cropping systems, potentially play in mitigating both NO − 3 leaching (Bryant et al 2019) and N 2 O emissions (de Klein et al 2019). Emerging questions from both reviews identify the need for further laboratory, field, and modelling research, in order to better understand the mechanisms of specific plants that show potential to reduce N losses to the wider environment.…”
Section: Prefacementioning
confidence: 99%
“…Modelling of agricultural systems is an essential tool in developing and understanding longterm mitigation options for NO − 3 and NO − 3 losses. This is demonstrated in the paper by Bryant et al (2019) where leachingfrom dairy systems is modelled, and the paper by Cheng et al (2019) that focuses on leaching from young stock finishing systems. The papers by Rugoho et al (2019), and Dalley et al (2019) in particular are a salient reminder that just because a plant has the potential to reduce N losses, it does not mean there will be concomitant benefits for livestock, and that scientists and policy makers must also consider unforeseen implications with respect to social and financial outcomes.…”
Section: Prefacementioning
confidence: 99%
“…Excess N intake by grazing cows predominantly (75–85%) is excreted in the form of urea in urine [ 5 ]. In addition to the metabolic cost of producing urea, the excretion of excess N in urine causes increased N 2 O emissions and NO 3 leaching from pastures [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diversification of pastures through inclusion of pasture herbs can reduce the urinary N excretion through lower dietary N intake and improved utilization of N in rumen [ 7 ]. It is possible to reduce the detrimental effects of intensive dairy farming through application of novel pasture systems and use of plants with high nutritive value and secondary metabolites [ 6 , 8 , 9 ]. Chicory with its pectin content may provide a highly effective synchronization of the fermentable carbohydrates and N in the rumen leading to improved rumen fermentation and lower nitrogen excretion from ruminants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%